Implied transaction costs by Leland option pricing model: a new approach and empirical evidence - Li, Steven; Abdullah, Mimi Hafizah (Macmillan Publishers Ltd., 2012)
Estimation of transaction costs in a stock market is an important issue for stock trading, asset pricing, stock market regulation and so on, and it is often done by combining the bid-ask spread estimate with commissions and other fees provided by market participants, which can be subjective. This study aims to offer an innovative alternative method to estimate the transaction costs in stock trading via the implied transaction costs by using the Leland option pricing model. The effectiveness of this new approach is tested by using the S&P/ASX 200 index call options data. On the basis of the actual transaction costs estimates on the Australian Securities Exchange (ASX) documented by previous studies and Roll’s model, the empirical results reveal that this new approach can provide a reliable transaction costs estimate on stock trading on the ASX. Furthermore, the accuracy of the implied transaction costs across option moneyness and maturity and the variation of the implied transaction costs during the recent global financial crisis period are investigated.